2000
DOI: 10.1080/096582100387678
|View full text |Cite
|
Sign up to set email alerts
|

Modality Effects and the Development of the Word Length Effect in Children

Abstract: Two experiments investigated the development of the word length effect in children aged 4 to 10 years, comparing auditory and visual stimuli. The question addressed was whether word length effects emerged earlier with auditory presentation or visual presentation, or whether they emerged at the same age regardless of presentation modality. Results provided evidence that word length effects emerge earlier with visual than auditory presentation. The implication of our results is that with visual presentation, 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 63 publications
6
36
0
Order By: Relevance
“…Firstly, word length effects have been observed in probed recall tasks where ordered recall of multiple items is not required (Avons, Wright & Pammer, 1994;Henry, 1991;Henry, Turner, Smith & Leather, 2000). As we have demonstrated with free recall, participants can adopt a serial recall strategy even though the instructions do not stress the use of order information, and to the extent that this is so, one would expect the standard word length effect.…”
Section: Word Length In Ltm 31mentioning
confidence: 93%
See 1 more Smart Citation
“…Firstly, word length effects have been observed in probed recall tasks where ordered recall of multiple items is not required (Avons, Wright & Pammer, 1994;Henry, 1991;Henry, Turner, Smith & Leather, 2000). As we have demonstrated with free recall, participants can adopt a serial recall strategy even though the instructions do not stress the use of order information, and to the extent that this is so, one would expect the standard word length effect.…”
Section: Word Length In Ltm 31mentioning
confidence: 93%
“…As we have demonstrated with free recall, participants can adopt a serial recall strategy even though the instructions do not stress the use of order information, and to the extent that this is so, one would expect the standard word length effect. A probe recall study by Henry et al (2000) illustrates this point. They examined the emergence of word length effects as a function of age.…”
Section: Word Length In Ltm 31mentioning
confidence: 95%
“…In Experiment 1, there was some evidence of an 'intermediate' strategy stage of phonological coding on its own (phonological similarity effects) followed by a later stage of phonological coding plus verbal rehearsal (phonological similarity and word length effects) in the cluster analysis. However, given the difficulties of interpreting word length effects as evidence for verbal rehearsal (Cowan et al, 1992;Henry, 1991;Henry et al, 2000;Yuzawa, 2001), the cautious conclusion is that both of these effects indicated phonological coding. In all other relevant analyses, phonological similarity and word length effects coincided in the older and more mature children.…”
Section: Additional Analysis Combining Span Scores For Experiments 1 mentioning
confidence: 99%
“…spoken duration or differences in phonological complexity -see Hulme, Neath, Stuart, Shostak, Surprenant & Brown, 2006;Lewandowsky & Oberauer, 2008;Mueller, Seymour, Kieras & Meyer, 2003;Romani, McAlpine, Olson, Tsouknida & Martin, 2005). Word length effects in picture span tasks emerge at 7-9 years (Halliday et al, 1990;Henry, Turner, Smith & Leather, 2000;Hitch, Halliday, Dodd & Littler, 1989;Hitch et al, 1991), although there is debate about the precise cognitive processes responsible for this development in relation to verbal rehearsal and verbal output (Cowan, Day, Saults, Keller, Johnson & Flores, 1992;Henry, 1991;Henry et al, 2000;Yuzawa, 2001). Others doubt that word length effects require articulatory processes (e.g.…”
mentioning
confidence: 99%
“…It is also worth noting that negative phonological similarity and word length effects have been reported in other studies of verbal short-term memory (Campoy & Baddeley, 2008;Carlesimo, Galloni, Bonanni, & Sabbadini, 2006;Copeland, & Radvansky, 2001;Fallon, Groves, & Tehan, 1999;Henry, Turner, Smith, & Leather, 2000;Lian, & Karlsen, 2004;Romani, McAlpine, Olson, Tsouknida, & Martin, 2005), and, crucially, often occur in the general adult population in conditions that increase task difficulty relative to traditional immediate serial recall methods (Copeland & Radvansky, 2001;Fallon et al, 1999;Lian & Karlsen, 2004;Romani et al, 2005). This may be because under such conditions participants adopt a strategy other than rehearsal, such as using the similarity between phonologically similar items as a cue to item identity (Fallon et al, 1999;Gupta, Lipinski, & Aktunc, 2005), or making use of semantic information that might be richer for long than for short words (Campoy & Baddeley, 2008).…”
Section: Discussionmentioning
confidence: 99%